Analisis Pengembangan Ekonomi Masyarakat Desa Bonto Salluang melalui Pengembangan Lobster Air Tawar - Nurwahidah; Muhammad Agung Ady Mangilep; Julius Jillbert; Daniella Cynthia Sampepajung; Fitriwati Djaman; Sanusi Fattah; Andi Baso Siswadarma (Universitas Islam Balitar, 2025)
Promoting the cultivation of freshwater lobsters presents an alternative strategy to boost economic development along the southern coast of Sulawesi Island. This study aims to examine the internal and external factors influencing the growth of the freshwater lobster industry, which can serve as a catalyst for business expansion. The research employs SWOT analysis, a method that assesses strengths, weaknesses, opportunities, and threats. From this analysis, eight potential policies for the development of freshwater lobsters were identified. The findings also indicate that the research area possesses significant potential and is well-suited for freshwater lobster cultivation.